Gastric volvulus post sleeve gastrectomy converted to gastric bypass in pregnancy: a case report - Ferris, Baillie W. C. (International Surgery Journal, 2018)
Complications arising from revision bariatric surgery can be complex due to altered anatomy. This is especially the case in a bariatric patient who becomes pregnant. I present an interesting case of a female patient who suffered a gastric volvulus during pregnancy after having had revision gastric bypass surgery 3 years prior, secondary to an internal hernia. This case highlights that revision bariatric surgery attracts a higher rate of complication, both preoperatively and long term, as well as highlighting the need for a high degree of suspicion for rare causes of abdominal pain in patients post bariatric surgery. Pregnancy is also an added risk factor for these patients.